Selection and characterization of mutational resistance to aztreonam/avibactam in β-lactamase-producing Enterobacterales. (26th September 2021) - Mushtaq, Shazad; Vickers, Anna; Ellaby, Nicholas; Woodford, Neil; Livermore, David M
Abstract: Background: Aztreonam/avibactam is being developed for its broad activity against carbapenemase-producing Enterobacterales, including those with metallo-β-lactamases (MBLs). Its potential to select resistance in target pathogens was explored. Findings are compared with previous data for ceftazidime/avibactam and ceftaroline/avibactam. Methods: Single-step mutants were sought from 52 Enterobacterales with AmpC, ESBL, KPC, MBL and OXA-48-like enzymes. Mutation frequencies were calculated. MICs were determined by CLSI agar dilution. Genomes were sequenced using Illumina methodology. Results: Irrespective of β-lactamase type and of whether avibactam was used at 1 or 4 mg/L, mutants could rarely be obtained at >4× the starting MIC, and most MIC rises were correspondingly small. Putative resistance (MIC >8 + 4 mg/L) associated with changes to β-lactamases was seen only for mutants of AmpC, where it was associated with Asn346Tyr and Tyr150Cys substitutions. Asn346Tyr led to broad resistance to avibactam combinations; Tyr150Cys significantly affected only aztreonam/avibactam. MIC rises up to 4 + 4 mg/L were seen for producers of mutant KPC-2 or -3 enzymes, and were associated with Trp105Arg, Ser106Pro and Ser109Pro substitutions, which all reduced the MICs of other β-lactams. For producers of other β-lactamase types, we largely found mutants with lesions in baeRS or envZ, putatively affecting drug accumulation. Single mutants had lesions in ampD, affecting AmpC expression or ftsI, encoding PBP3. Conclusions: The risk of mutational resistance to aztreonam/avibactam appears smaller than for ceftazidime/avibactam, where Asp179Tyr arises readily in KPC enzymes, conferring frank resistance. Asn346 substitutions in AmpC enzymes may remain a risk, having been repeatedly selected with multiple avibactam combinations in vitro .